Analisis Inflation Targeting Framework (ITF) dan Perubahan Respon Kebijakan Moneter - Pasaribu, Ayu Angelina; Pratomo, Wahyu Ario; Tanjung, Ahmad Albar (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The purpose of this study is to determine how the implementation of inflation targeting framework (ITF) and how the changes in monetary policy response. The data period starts from 2014 to 2023, with monthly data. The data analysis method used is a model of two interrelated simultaneous equations, called Two Stage Least Square (2SLS). The results of this study explain that the exogenous variables in the first equation of real interest rates, inflation, inflation gap, output gap have a positive and significant effect on the BI rate. Exogenous variables in the second equation, namely inflation target, BI rate, exchange rate, WTI world oil price have a positive and significant effect on inflation. However, the output gap has a negative and significant effect on inflation, and the money supply has no significant effect on inflation. The change in monetary policy response is seen from the increase or decrease of BI rate by 25 Basis points.